NPM, 'DIE HARD' LEGACY? NPM REFORM AND ADMINISTRATIVE LAW IN KOREA. (18th September 2013) - Hong, Joon‐Hyung; Haque, M. Shamsul; Turner, Mark
SUMMARY Regardless of whether neoliberalism has declined or whether it is still appropriate to say 'neoliberal', it is highly probable that New Public Management (NPM) reform will continue and survive challenges in Korea. By analyzing the relationship between the NPM‐based government reforms and role of administrative law during the last decades in Korea, the article tries to explain notable persistence of those legacies of the NPM reforms. Financial emergencies, such as the 1997 foreign currency crisis in Korea and economic downturn in recent years, could repeat themselves at any time. Government reform will then continue to be a surviving toolkit to cope with such crises. Another factor is citizens' desire and expectation, which is taxpayers' demand. With this undiminished, ever‐increasing demand for better quality of public service, there could be no way out but to reform government by downsizing and restructuring itself in the name of efficiency and accountability. NPM‐based government reform has risks and uncertainty problems, however, as long as success cannot be guaranteed by public trust in government. The article concludes by confirming the value of constitutionalism and the Rule of Law that constitute indispensable and soundest means to build trust, which is a critical success factor in government reforms. Copyright © 2013 John Wiley & Sons, Ltd.